1999
DOI: 10.1023/a:1005180027451
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Molecular dynamics simulations of three model lipid monolayers of 2,3-diacyl-D-glycerolipids, that contained stearoyl (18:0) in the position 3 and oleoyl (18:ω9cis), linoleoyl (18:2ω6cis), or linolenoyl (18:3ω3cis) in the position 2, have been carried out. The simulation systems consisted of 24 lipid molecules arranged in a rectangular simulation cell, with periodic boundary conditions in the surface plane. 1 nanosecond simulations were performed at T = 295 K. C-C and C-H bond order parameter profiles and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…However, with increasing lipid unsaturation the fraction of the free volume is found to increase in the middle of the membrane and decrease in the outer part of the apolar phase. This finding is consistent both with our previous results 59, [73][74][75] and with experimental data, 76,77 and can be explained by the fact that due to the increasing flexibility of the hydrocarbon tails when containing more methylene-interrupted C v C double bonds [73][74][75] these unsaturated tails do not extend to the middle of the membrane. 59 The analysis of the percolation of the voids has revealed that the preformed cross-membrane channels are not broad enough to let small molecules, such as water, go readily through them, however, they are likely to facilitate the permeation of such molecules across the membrane.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, with increasing lipid unsaturation the fraction of the free volume is found to increase in the middle of the membrane and decrease in the outer part of the apolar phase. This finding is consistent both with our previous results 59, [73][74][75] and with experimental data, 76,77 and can be explained by the fact that due to the increasing flexibility of the hydrocarbon tails when containing more methylene-interrupted C v C double bonds [73][74][75] these unsaturated tails do not extend to the middle of the membrane. 59 The analysis of the percolation of the voids has revealed that the preformed cross-membrane channels are not broad enough to let small molecules, such as water, go readily through them, however, they are likely to facilitate the permeation of such molecules across the membrane.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the central part of the bilayer is rather compact, i.e., there are considerably less voids among the CH 3 groups than among the chains of CH 2 groups. However, the central part of the membrane becomes more loosely packed with increasing unsaturation of the lipid molecules, in accordance with our previous finding that polyunsaturated sn-2 chains are characterized by very high equilibrium flexibility, [73][74][75] and hence do not penetrate as deep into the bilayer as the saturated sn-1 chains even if they consist of more carbon atoms. 59 This high flexibility of the chains consisting of methylene-interrupted C v C double bonds can also explain the deepening of the minimum of the profiles at the outer part of zone 1 with increasing lipid unsaturation.…”
Section: -8supporting
confidence: 92%
See 1 more Smart Citation
“…The PU FA tails of lipids are of great importance for the structure and functioning of biomembranes [179][180][181][182][183][184][185][186]. Docosahexaenoic acid, 22 : 6(n 3)cis, is the longest and most unsaturated FA commonly found in nature.…”
Section: Bilayers: Lipids With Saturatedmentioning
confidence: 99%
“…Many theoretical investigations (during the period of last 7 years) were devoted to the various properties of unsaturated and PU FA chains of different lipid molecules in bilayers; several FA chains most fre quently studied by molecular simulations and corre sponding references are enumerated below: 22 : 6(n 3)cis [181,[192][193][194][195][196][197][198][199][200][201][202][203][204], 22 : 5(n 3)cis [192], 20 : 4(n 6)cis [64, 195, 198, 200-203, 205, 206], 18 : 3(n 3)cis [195,198,200,201,203], 18 : 2(n 6)cis [64,195,198,[200][201][202][203]207], 18 : 1(n 9)cis [54, 55, 59, 64, 74, 88, 181, 194-196, 198, 200-203, 205, 208-231].…”
Section: Bilayers: Lipids With Saturatedmentioning
confidence: 99%